Aqueous ammonium-iodine battery
By introducing ammonium ions and organic material PTCDI into ammonium iodine batteries, the dendrite growth, low anode utilization and corrosion problems of traditional metal-iodine batteries are solved, and high cycle stability and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411688497.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional metal-iodine batteries have problems with dendrite growth, low anode utilization rate and susceptible to electrolyte corrosion, which affects the energy density, power density and cycle stability of the battery.
Using the high stability and rapid transmission kinetic characteristics of ammonium ions interlayer/extraction between organic materials, combined with the inert characteristics to iodine ions, an ammonium iodine battery structure was designed, using I2@AC as the positive electrode material, PTCDI or PTCDA is used as the negative electrode material, and a mixed solution of ammonium sulfate and ammonium iodide is used as the electrolyte.
The dendrite-free design is realized, the utilization rate of the negative electrode is improved, the anode is avoided, and the corrosion of the anode is shown is high cycle stability and excellent electrochemical properties, including high capacity retention and good rate performance.
Smart Images

Figure CN119447515A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aqueous ammonium iodine batteries, and in particular to an aqueous ammonium iodine battery structure for cooperative energy storage of ammonium iodine ions. Background Art
[0002] With the development of the times, the excessive consumption of non-renewable energy and the resulting ecological and environmental pollution problems are becoming increasingly serious worldwide. The development of sustainable and environmentally friendly energy storage systems has received close attention from researchers in recent years. Iodine is environmentally friendly and a rich natural resource (the content in seawater is 50-60μg / L -1 ), simple conversion reaction mechanism (I2 + 2e - ↔ 2I - ) and a high theoretical capacity (1040 mAh cm -3 and 211 mAh g -1 ) and has been widely studied. Compared with traditional intercalation-type positive electrode materials, iodine exhibits fast and reversible conversion chemistry, avoiding the problem of slow multivalent cation intercalation and easy collapse of the host material structure due to strong electrostatic interactions. However, the inherent dendrite growth problem of metal anodes not only leads to a significant loss in battery energy density and power density, but also directly affects the cycle stability of the battery. In addition, with regard to zinc-iodine batteries, previous studies generally use thicker zinc foil (thickness greater than 100 μm) as the zinc metal anode, which usually results in low utilization of the zinc anode. In addition, the zinc anode is susceptible to corrosion by the electrolyte, as well as I3 - and I5 - The shuttling problem also hinders the development of iodine batteries. Due to these shortcomings of traditional metal-iodine batteries, developing a battery structure that avoids interference from dendrite growth, is not corroded by iodine ions, and has high negative electrode utilization is an important research direction for the future development of iodine batteries.
[0003] In recent years, non-metallic ammonium ions (NH4 + ) due to its abundant resources and low molar mass (18 gmol -1 ) and small size of hydrated ions, it is considered to be a potential charge carrier for energy storage systems and is suitable for the development and application of aqueous batteries. Compared with the severe zinc dendrite growth inherent in zinc-iodine batteries, NH4 + It exhibits unique intercalation behavior due to the formation / breaking of hydrogen bonds. In addition, it contains rich NH4 +The battery system with electrolyte can operate normally under neutral or weakly acidic conditions. The introduction of ammonium ions in the iodine battery structure can first avoid the impact of metal anode dendrite growth on battery stability and the resulting energy density loss problem, and the problem of low utilization of traditional metal anodes will also be improved, and the negative electrode utilization of the battery system will be improved to a certain extent. Secondly, the rapid intercalation / deintercalation kinetics of ammonium ions effectively compensate for the inherent insulating properties of iodine. Finally, using materials that are inert to iodine ions as anodes can effectively eliminate the problem that traditional metal anodes are susceptible to electrolyte corrosion. Summary of the invention
[0004] The purpose of the present invention is to propose an ammonium iodine battery energy storage structure. The high stability and rapid transmission kinetics of ammonium ion intercalation / extraction between organic material layers represented by PTCDI are utilized, as well as their inert characteristics to various iodine ions. This ammonium iodine battery structure effectively avoids the common dendrite growth problems of metal anodes in metal-iodine batteries, the susceptibility to corrosion by iodine-containing electrolytes, and the low anode utilization rate. In addition, the ammonium ion intercalation / extraction between PTCDI layers exhibits high stability and rapid transmission kinetics, effectively compensating for the inherent insulating properties of iodine. The constructed ammonium iodine battery has an excellent cycle life and a high reversible specific capacity, and exhibits excellent electrochemical performance. Specifically, the specific technical scheme for implementing the present invention is as follows: The present invention provides an aqueous ammonium iodine battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode material is I2@AC, the negative electrode material is 3,4,9,10-perylenetetracarboxylic acid diimide (PTCDI) or 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), and the electrolyte is a mixed solution of ammonium sulfate ((NH4)2SO4) and ammonium iodide (NH4I), in which the ammonium sulfate concentration is 0.4-0.6M and the ammonium iodide concentration is 0.08-0.12M; the I2@AC is I2 encapsulated by activated carbon.
[0005] For the aqueous ammonium iodine battery described above, preferably, the positive electrode is prepared by the following method: Step (1): weigh I2 and grind and mix in air at 20-30°C for 1-10 min; Step (2): The mixed powder of I2 and activated carbon (AC) is shaken and sealed in a vacuum quartz tube, and heated at 70-100°C for 2-6h; Step (3): After waiting for natural cooling, activated carbon-encapsulated I2, i.e., I2@AC, is obtained; Step (4): The obtained I2@AC composite material is made into a slurry and coated on a cut substrate; the substrate is graphite paper or titanium sheet.
[0006] Step (5): drying in a vacuum drying oven to finally obtain the positive electrode of the ammonium iodine battery.
[0007] For the aqueous ammonium iodine battery described above, preferably, the mass ratio of I2 to AC in step (2) is 1-2:1.
[0008] For the aqueous ammonium iodine battery described above, preferably, in the step (4), the I2@AC is made into a slurry by mixing the I2@AC powder obtained in the step (3) with acetylene black, polyvinylidene fluoride and N-methylpyrrolidone (NMP), and then oscillating in a vortex oscillator.
[0009] For the aqueous ammonium iodine battery described above, preferably, the drying temperature in step (5) is 20-40° C., and the drying time is 6-10 hours.
[0010] For the aqueous ammonium iodine battery described above, preferably, the negative electrode is prepared by the following method: 3,4,9,10-perylenetetracarboxylic diimide (PTCDI) or 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) is made into a slurry and coated on a cut substrate, and dried in a vacuum drying oven to finally obtain an ammonium iodine battery negative electrode. Among them, the preferred drying temperature is 40-60°C and the drying time is 1-2 hours. The substrate is graphite paper or titanium sheet.
[0011] Preferably, the slurry described in the present invention is prepared by mixing the positive electrode material (I2@AC) or negative electrode material (PTCDI or PTCDA) powder, acetylene black and polyvinylidene fluoride, and then adding N-methylpyrrolidone to make a slurry. The mass ratio of the positive electrode material or negative electrode material, acetylene black and polyvinylidene fluoride is (7-8): (1-3): (1-3), and when the mass of the positive electrode material (I2@AC) or the negative electrode material (PTCDI or PTCDA) is 0.02-0.04g, the volume amount of N-methylpyrrolidone (NMP) is 0.5mL.
[0012] The present invention introduces ammonium ions as energy storage carriers based on iodine batteries. -1 ) and small size of hydrated ions, and is considered suitable for the development and application of aqueous batteries. + Due to the formation / breakage of hydrogen bonds, the unique intercalation behavior is exhibited, which avoids the dendrite growth caused by metal ion stripping and deposition in traditional metal-iodine batteries, which in turn causes the battery to short-circuit and fail, seriously affecting the electrochemical performance of the battery. The present invention utilizes the high stability of ammonium ions in the interlayer intercalation / extraction of organic materials represented by PTCDI, and the replacement of metal ions by non-metallic ions to avoid the problem of dendrite growth of the metal negative electrode, and realizes the dendrite-free design of the iodine battery structure.
[0013] The beneficial effects of the present invention are: 1. The ammonium iodine battery structure based on I2@AC positive electrode and PTCDI negative electrode of the present invention is 10 A g -1 The current density was as high as 242 mAh g -1 The capacity of the positive electrode was 2.377 W (based on the mass of iodine loaded on the positive electrode), and the capacity retention rate was 80.7% after about 2000 cycles.
[0014] 2. The ammonium iodine battery structure of the present invention avoids the problem of dendrite growth of the metal negative electrode by replacing metal ions with non-metallic ions, and realizes the non-dendrite design of the iodine battery structure. In addition, the organic materials represented by PTCDI are inert to iodine ions in the electrolyte, which avoids the problem that the negative electrode is susceptible to corrosion by the electrolyte. The rapid ion diffusion kinetics and high cycle stability of the ammonium iodine battery are achieved.
[0015] 3. The ammonium iodine battery structure of the present invention introduces NH4 into the system + The high stability and fast transmission kinetics of interlayer intercalation / extraction of organic materials represented by PTCDI make up for the insulating properties of traditional iodine and are more conducive to the cycle stability of the battery.
[0016] 4. Compared with traditional metal-iodine batteries represented by zinc-iodine batteries, the ammonium-iodine battery structure of the present invention has the advantages of low cost (high negative electrode utilization), environmental friendliness, and high safety, and has great application potential in the field of electrochemical energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A working principle diagram of the aqueous ammonium iodine battery provided by the present invention; Figure 2 This is a thermogravimetric test diagram of the I2@AC positive electrode material used in the ammonium iodine structure battery of the present invention; Figure 3 This is a test diagram of the specific surface area of the I2@AC positive electrode material used in the ammonium iodine structure battery of the present invention; Figure 4 The GCD curves of the ammonium iodine structure battery of the present invention at different current densities; Figure 5 CV curves of the ammonium iodine structure battery of the present invention at different scanning rates; Figure 6 The ammonium iodine structure battery of the present invention is 10A g -1 Charge and discharge cycle stability curve at current density.
[0018] Figure 7 The figure is a rate performance test curve of the ammonium iodine battery of the present invention at different current densities.
[0019] Figure 8 Comparative Example 1: Zinc-iodine battery based on zinc foil negative electrode at 10 A g -1 Charge and discharge cycle stability curve at current density.
[0020] Fig. 9 This is the rate performance test curve of the zinc-iodine battery based on zinc foil negative electrode at different current densities in Comparative Example 1.
[0021] Fig.10 Comparative Example 2: The zinc-iodine battery based on zinc powder negative electrode at 10 A g -1 Charge and discharge cycle stability curve at current density.
[0022] Fig.11 This is the rate performance test curve of the zinc-iodine battery based on zinc powder negative electrode at different current densities in comparative example 2. DETAILED DESCRIPTION
[0023] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention. Example 1
[0024] The present invention proposes an ammonium iodine battery energy storage structure based on an I2@AC positive electrode and a PTCDI negative electrode, and its material preparation and experimental implementation include the following steps: (1) Weigh I2 and grind and mix directly at room temperature for 5-10 min.
[0025] (2) The powder obtained in step (1) was evenly mixed with AC powder and stirred for 10 min.
[0026] (3) The mixed powder obtained in step (2) was sealed in a 20 ml vacuum quartz tube and heated at 80 °C for 4 hours.
[0027] (4) The I2@AC powder obtained in step (3) was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, wherein the mass of the I2@AC powder was 20 mg, 0.5 mL of NMP was added, and then vortexed on a vortex oscillator for 1 hour.
[0028] (5) The uniformly dispersed slurry obtained in step (4) is coated on a 1 cm*1 cm titanium sheet and dried in a vacuum drying oven at 40°C for 8 hours to obtain an I2@AC positive electrode. The thermogravimetric characterization results of I2@AC in Example 1 are shown in FIG. Figure 2As shown in the figure, it shows the sublimation of iodine loaded in I2@AC as the temperature increases. It can be obtained that the content of I2 in the I2@AC prepared by us is 50% of the mass of I2@AC. Figure 3 Shown are the specific surface area test results, indicating the successful adsorption of iodine in AC.
[0029] (6) Prepare a PTCDI negative electrode slurry in a similar manner to step (4). The uniformly dispersed slurry is coated on a 1 cm*1 cm titanium sheet and dried in a vacuum drying oven at 60°C for 1 hour to obtain a PTCDI negative electrode.
[0030] (7) A mixed solution of ammonium sulfate and ammonium iodide is used as the electrolyte of the ammonium iodine battery structure, wherein the concentration of ammonium sulfate is 0.5M, the concentration of ammonium iodide is 0.1M, I2@AC is the positive electrode of the ammonium iodine battery structure, and PTCDI is used as the negative electrode material of the structure. Figure 4 The GCD curve of the assembled ammonium iodine battery is shown. It can be seen that there are several pairs of GCD platforms. Figure 5 is its CV curve, the redox peak position and Figure 4 The GCD platform result corresponds to 10 A g -1 The charge-discharge cycle stability curve at a current density of Figure 6 As shown in the figure, after nearly 2000 cycles, the capacity can maintain 80.7% of the initial capacity. The energy density remains at 200 Wh kg throughout the cycle. -1 The above is the PTCDI rate performance results. Figure 7 As shown. When the current density is increased from 18 A g −1 Reduced to 5 Ag −1 Then gradually increase to 18 A g -1 During the process, the capacity retention rates were 95.3%, 88.9%, 82.9%, 72.1% and 58.7%, respectively. The assembled ammonium iodine battery structure has high reversible specific capacity and excellent cycle stability. Example 2
[0031] The mass of I2@AC powder in the I2@AC positive electrode slurry preparation method in step (4) of Example 1 was changed to 40 mg, and the oscillation time in the vortex oscillator was replaced with 2 h. The remaining technical features were the same as those in Example 1. Example 3
[0032] The mass ratio of the I2@AC mixed powder to acetylene black and polyvinylidene fluoride in the I2@AC positive electrode slurry preparation method in step (4) of Example 1 is replaced with 7:2:1. The remaining technical features are the same as those of Example 1. Example 4
[0033] The I2 and AC powders in step (3) of Example 1 were sealed in a 20 ml vacuum quartz tube, and the heating time was changed to 6 hours. The remaining technical features were the same as those of Example 1. Example 5
[0034] The I2 and AC powders in step (3) of Example 1 were sealed in a 20 ml vacuum quartz tube, and the heating temperature was changed to 100° C. The remaining technical features were the same as those of Example 1. Comparative Example 1
[0035] This comparative example provides a zinc-iodine battery structure test case.
[0036] A 1M solution of zinc trifluoromethanesulfonate (Zn(CF3SO3)2) and a 0.05M solution of zinc iodide were used as the electrolyte for the zinc-iodine battery comparison structure, I2@AC was used as the positive electrode of the battery structure, and zinc foil (thickness > 0.1mm) was used as the negative electrode material of the zinc-iodine battery. The results showed that at 10 A g -1 The charge-discharge cycle stability curve at a current density of Figure 8 As shown in Figure 2, after nearly 2,000 cycles, the capacity retention rate is only 56%. Fig. 9 As shown. When the current density is increased from 18 A g −1 Reduced to 5 Ag −1 Then gradually increase to 18 A g -1 In the process of this comparative experiment, the capacity retention rates were only 19.2%, 24.4%, 18.3%, 6.7% and 3.0%, respectively. Figure 7 It is shown that the capacity retention rate of the PTCDI rate performance test of Example 1 of the present invention is much lower. Comparative Example 2
[0037] This comparative example provides a zinc-iodine battery structure test case.
[0038] A mixed solution of 1 M zinc trifluoromethanesulfonate and 0.05 M zinc iodide was used as the electrolyte for the zinc-iodine battery comparison structure, I2@AC was used as the positive electrode of the zinc-iodine battery structure, and zinc powder was used as the negative electrode material of the zinc-iodine battery. The preparation process of the zinc powder negative electrode sheet refers to step (4) of Example 1. The charge and discharge cycle stability curve of the assembled battery is shown in Fig.10 As shown in the figure, after nearly 2000 cycles, the capacity retention rate is only 55.2%. Fig.11 As shown, when the current density is increased from 18 A g −1 Reduced to 5 A g −1 Then gradually increase to 18 A g -1 In the process, the capacity retention rates in this comparative experiment were only 10.8%, 3.7%, 1.6%, 2.8% and 6.7%, respectively. Figure 7 It is shown that the capacity retention rate of the PTCDI rate performance test of Example 1 of the present invention is much lower.
[0039] Comparative Examples 1 and 2 show metal zinc-iodine batteries, which use I2@AC as the positive electrode like the ammonium iodine battery of the present invention, but the negative electrode is different. Comparative Examples 1 and 2 use zinc foil and zinc powder as metal negative electrodes, and the present invention uses PTCDI as the negative electrode. The present invention avoids the problem of dendrite growth of the metal negative electrode by replacing the metal ions with non-metallic ions-ammonium ions, and realizes the dendrite-free design of the iodine battery structure. In addition, the organic materials represented by PTCDI are inert to the iodine ions in the electrolyte, which avoids the problem that the negative electrode is susceptible to corrosion by the electrolyte. The fast ion diffusion kinetics and high cycle stability of the non-metal-iodine battery are realized.
[0040] In the technical solution of the present invention, although the above embodiments provide options for positive and negative electrode materials of the battery structure with better effects, such as I2@AC as an iodine storage positive electrode material, and PTCDI as an organic material as a negative electrode material of the present ammonium iodine battery structure. However, the present invention is not limited to the selection of positive and negative electrode materials in the above embodiments, and the selection of specific positive and negative electrode materials needs to be determined according to the material properties; for example, the embodiment provides the oscillation time of the slurry in the vortex oscillator, but the present invention is not limited to the oscillation time in the vortex oscillator given in the above embodiments. That is, the content claimed for protection by the present invention shall be based on the scope recorded and explained in the claims.
[0041] It should be noted that the above-described embodiments of the present invention are only explanations and clarifications for those skilled in the art to understand the technical essence of the present invention, so the technical contents described are not intended to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modifications, equivalent substitutions and improvements based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.
Claims
1. An aqueous ammonium iodine battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein: The positive electrode material is I2@AC, the negative electrode material is 3,4,9,10-perylenetetracarboxylic acid diimide or 3,4,9,10-perylenetetracarboxylic acid dianhydride, the I2@AC is I2 encapsulated by activated carbon, and the electrolyte is a mixed solution of ammonium sulfate and ammonium iodide.
2. The aqueous ammonium iodine battery according to claim 1, characterized in that: The positive electrode is prepared by the following method: Step (1): weigh I2 and mix and grind it in air at 20-30°C for 5-10 min; Step (2): shake the I2 and AC mixed powders and seal them in a vacuum quartz tube, and heat them at 70-100°C for 2-6h; Step (3): After waiting for natural cooling, activated carbon-encapsulated I2, i.e., I2@AC material, is obtained; Step (4): preparing the obtained I2@AC material into a slurry and coating it on a substrate to obtain an I2@AC positive electrode sheet; Step (5): Dry the I2@AC positive electrode sheet in a vacuum drying oven to finally obtain the positive electrode of the ammonium iodine battery.
3. The aqueous ammonium iodine battery according to claim 2, characterized in that: In the step (2), the mass ratio of I2 to AC is 1-2:
1.
4. The aqueous ammonium iodine battery according to claim 2, characterized in that: In the step (4), the I2@AC is prepared into a slurry by mixing the I2@AC obtained in the step (3) with acetylene black, polyvinylidene fluoride and N-methylpyrrolidone, and then oscillating in a vortex oscillator.
5. The aqueous ammonium iodine battery according to claim 2, characterized in that: The drying temperature in step (5) is 20-40° C. and the drying time is 6-10 hours.
6. The aqueous ammonium iodine battery according to claim 1, characterized in that: The negative electrode is prepared by the following method: 3,4,9,10-perylenetetracarboxylic acid diimide or 3,4,9,10-perylenetetracarboxylic acid dianhydride is made into slurry and coated on a cut substrate, and dried in a vacuum drying oven to finally obtain the negative electrode of the ammonium iodine battery.
7. The aqueous ammonium iodine battery according to claim 6, characterized in that: The vacuum drying temperature is 40-60°C and the drying time is 1-2 hours.